Adjunctive diagnostic techniques for oral lesions of unknown malignant potential: Systematic review with meta‐analysis. Issue 5 (5th May 2014) - Fuller, Colin; Camilon, Ryan; Nguyen, Shaun; Jennings, Jon; Day, Terry; Gillespie, M. Boyd
ABSTRACT: Background: The purpose of this study was to critically review the published evidence concerning adjunctive diagnostic techniques in the diagnosis of oral lesions of unknown malignant potential. Methods: We conducted a systematic literature review with meta‐analysis using PubMed to search for articles published from June 1993 through June 2013 to identify prospective studies evaluating any diagnostic method, with tissue biopsy confirmation, in clinically evident oral lesions of unknown malignant potential. Aggregate weighted totals and SEs for true, false‐positive, false‐negative, and inadequate results were calculated and compared among subgroups. Results: Forty‐eight articles satisfying inclusion criteria were identified. Twenty‐five were included in quantitative synthesis. Conclusion: Oral cytology holds higher diagnostic value than specialist's oral examination, which holds higher value than in vivo toluidine blue staining. This study does not support the use of computer‐aided or liquid‐based cytology. Future studies should be designed to test multiple methods in the same patient population to allow direct comparison among various techniques. © 2014 Wiley Periodicals, Inc. Head Neck 37: 755–762, 2015